Kyrgyz Republic : Joint Staff Advisory Note on the Poverty Reduction Strategy Paper. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2012)
The paper focuses on the workings of the Medium-Term Development Program (MTDP) of the Kyrgyz Republic. Raising living standards as well as taking measures for reducing poverty have been cited as the main priority areas of the strategy, and the measures to be undertaken to bring about improvements in these areas are highlighted. The report also throws light on the major objectives of MTDP's three-year strategy during the period from 2012-14.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet